Direct determination of retrotransposon transposition rates in Drosophila melanogaster. - Nuzhdin, S.V.; Mackay, T.F.C. (Genetics research, 1994)
Rates of transposition and excision of the Drosophila melanogaster retrotransposon elements mdg3, 297, Doc, roo and copia were estimated directly, by in situ hybridization analysis of their cytological insertion sites in 31 replicates of a highly inbred line that had accumulated spontaneous mutations for approximately 160 generations. Estimated transposition rates of Doc, roo and copia were, respectively, 4.2 x 10(-5), 3.1 x 10(-4) and 1.3 x 10(-3); no transpositions of 297 nor mdg3 were observed. Rates of transposition of copia varied significantly among sublines. Excisions were only observed for roo elements, at a rate of 9.0 x 10(-6) per element per generation. Copy number averaged over these element families increased 5.9%; therefore, in these lines the magnitude of the forces opposing transposable element multiplication were weaker than transposition rates. Estimated total genomic mutation rates from transposition are of the same order as the nucleotide mutation rate in this species.